2018
DOI: 10.1029/2018wr023285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Runoff Variability and Sea Level on Saltwater Intrusion: A Case Study of Nandu River Estuary, China

Abstract: Saltwater intrusion exits in estuary areas. Significant change in runoff variability (RV) has been detected in many basins, but limited research has investigated this change's effect on downstream saltwater intrusion. Using measured time series, this study has statistically detected a significant trend of increased RV and sea level (SL) rise in Nandu River Estuary, China, and analyzed their effect on the saltwater intrusion combining the Finite Volume Community Ocean Model and Monte Carlo method. The Mann-Kend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Previous studies have investigated changes in SWI in several estuaries and deltas worldwide. River discharge variability and SLR have been found to be the main factors enhancing salinity intrusion in the Yangtze, Pearl, Changjiang, Mekong, Ganges, Brahmaputra, Meghna, and Nandu rivers (Akter et al., 2019; Bricheno & Wolf, 2018; Chen et al., 2016; He et al., 2018; Hong et al., 2020; Liu et al., 2019; Smajgl et al., 2015; Zhu et al., 2018). The results of this study confirm such general behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated changes in SWI in several estuaries and deltas worldwide. River discharge variability and SLR have been found to be the main factors enhancing salinity intrusion in the Yangtze, Pearl, Changjiang, Mekong, Ganges, Brahmaputra, Meghna, and Nandu rivers (Akter et al., 2019; Bricheno & Wolf, 2018; Chen et al., 2016; He et al., 2018; Hong et al., 2020; Liu et al., 2019; Smajgl et al., 2015; Zhu et al., 2018). The results of this study confirm such general behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The gravitational circulation was mainly caused by the baroclinic effect of density gradient. Equations (1) and (2) showed that the residual circulation and the gravitational circulation differed by the depth-averaged residual current and it should be zero if the gravitational circulation velocity in vertical was integrated along the water depth. The same method as the calculation of gravitational circulation was used to calculate the salinity, to reflect the distribution rule of the time-averaged salinity in the vertical direction.…”
Section: Circulation Characteristics Under Tidal Range Changementioning
confidence: 99%
“…As one of the basic topics of estuarine dynamics research, the mixing of salt-fresh water has always aroused the concern of academic and engineering circles. With the changes in natural conditions such as global warming [1] and sea level rise [2,3], as well as the impact of human activities, including the construction of reservoirs and dams [4] and the excavation of navigation channels [5], the estuarine conditions will be adjusted briefly or slowly, and the mixed state of salt-fresh water will also change. These changes have an important impact on flow structure, estuarine ecology [6][7][8], and sediment movement [9].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the magnitude of the flow not only causes an increase in the concentration of pollutants, but also allows the intrusion of the saline wedge into the river, which produces an increase in salinity levels. Some aquatic species are more sensitive to changes in quality standards, resulting in loss in biodiversity and ecosystem services (Wang et al, 2015;Mosley, 2015;Huang et al, 2015;He et al, 2018;Fonseca et al, 2020).…”
Section: Introductionmentioning
confidence: 99%